SPARSH: a camp based approach for orthopaedic disabilities and its success in central India - Singhal, Prakhar; Mishra, Santosh Kumar; Shukla, Jiten; Verma, Rahul; Gohiya, Ashish (International Journal of Research in Orthopaedics, 2020)
Background: Around 15% of population in the world is living with disability. The present study was carried out during the special project for assistance, rehabilitation and strengthening of handicapped (SPARSH) camp to know the current pattern of locomotor disability and to observe the outcome of the camp surgeries for the correction of deformity. Methods: This prospective observational cross-sectional study was conducted at the department of orthopaedics and traumatology Gandhi Medical College at SPARSH camp organised by the Government of M. P. at J. K. hospital Bhopal. All the patients with locomotor disability attending the SPARSH camp irrespective of age, sex and cause, were included in the study Results: In total 287 patients attended the camp in which majority of the patients were suffering from cerebral palsy. 107 patients were selected for operative intervention in which tendo-achilles lengthening was performed most commonly. Conclusions: The corrective surgical camp provides an avenue of healthcare opportunity for the underprivileged sector of society. A camp based approach helps in identification, gradation & rehabilitation of orthopaedic deformities.